Autism spectrum disorder – the fight of the public against a disease it fails to understand - Ahmed, Minahel; Sikandar, Eman; Javid, Arysha (Journal of the Pakistan Medical Association, 2024)
Madam, Autism is a heterogeneous set of neurodevelopmental conditions affecting around 1% of the population globally [1,2] and every 1 in 120 people in Pakistan [5]. It exhibits a higher incidence in males than females [1,2,5]; this may be because males have a lower threshold for brain dysfunction, and require a lower genetic burden to cause autism, than females. Individuals with autism commonly experience impaired social cognition and perception, atypical information processing, and restricted patterns of behaviour and interest. A study from The Lancet in 2014 determined that the autism goes hand in hand with multiple other intellectual, psychiatric, medical, and behavioural disorders, with a significant association between autism and motor abnormality, sleep disorders, and aggressive behaviours [1]. While multiple genetic and developmentally early environmental factors have been established as risk factors in the aetiology of autism, none were confirmed to be adequate alone for ASD to develop. With respect to familiarity with autism, while people are not completely unaware of the existence of the disease they do display poor knowledge about its symptoms and presentation. In a study conducted in Pakistan in 2012, 52 out of the 73 teachers who participated (71%) claimed to have knowledge regarding autism; substantial gaps were recognized in their perceived knowledge about the disease [3]. Another study conducted in Karachi also concluded that parents’ lack of awareness and insufficient knowledge among parents about the signs and symptoms as well as the treatment and diagnosis of autism [4]. Early diagnosis is crucial for timely intervention; the assessment of children needs to be developmental and multidisciplinary [1]. Even though multiple rating scales and checklists have been established, it is preferable to use more performance-based methodologies for assessment and diagnosis [2]. Thorough and focused behavioral interventions in early life can promote social communication and decrease aggression and anxiety in individuals diagnosed with ASD. Support should be personalized according to each individual and if feasible, should be multi-dimensional. Although drugs as a form of treatment diminish comorbid symptoms in autistic people, they alone display no direct effect on enhancing social communication. Awareness can be spread by donating or volunteering at fundraisers, through social media, and by participating in various autism programs. Formation of an encouraging environment that acknowledges and respects that the individual is different is imperative.